The interplay of technological innovation and business model innovation toward company performance - Smajlović, Selma (Array, 2019)
This study aims to clarify the relation between technological innovation and business model innovation and their shared impact on the business success of medium and large enterprises. Drawing on the Resource-Based View, this paper offers a comprehensive research model that analyses the relationships between technological innovation and business model innovations and their impact on business success. Structural Equation Modelling is utilized for the analysis of a dataset collected in a Southeast European developing country among medium and large enterprises. The results show that technological innovation has a positive influence on business model innovation and that business model innovation positively impacts the success of a business. Finally, the results confirm the mediating role of business model innovation between technological innovation and company business success. This research adds to the existing literature by empirically investigating the relationship between technological innovation, business model innovation, and company success identifying an antecedent role in the relationship between technological innovation and business model innovation.